2014
DOI: 10.1186/1743-422x-11-14
|View full text |Cite
|
Sign up to set email alerts
|

First genome sequences of Achromobacter phages reveal new members of the N4 family

Abstract: BackgroundMulti-resistant Achromobacter xylosoxidans has been recognized as an emerging pathogen causing nosocomially acquired infections during the last years. Phages as natural opponents could be an alternative to fight such infections. Bacteriophages against this opportunistic pathogen were isolated in a recent study. This study shows a molecular analysis of two podoviruses and reveals first insights into the genomic structure of Achromobacter phages so far.MethodsGrowth curve experiments and adsorption kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 76 publications
2
59
0
1
Order By: Relevance
“…10,[17][18][19] However, a survey of recent studies comparing codon usage by phages and their hosts revealed a mixture of studies where the presence of tRNA genes corresponds to codons overly expressed by the phage compared to its host 10,[20][21][22][23] and studies where that is not the case. [24][25][26][27] In phage PVP-SE1, only 11 of the codons associated with its 24 tRNA genes were present at a frequency higher than in its Salmonella hosts.…”
Section: Codon Versus Amino Acid Usagementioning
confidence: 99%
“…10,[17][18][19] However, a survey of recent studies comparing codon usage by phages and their hosts revealed a mixture of studies where the presence of tRNA genes corresponds to codons overly expressed by the phage compared to its host 10,[20][21][22][23] and studies where that is not the case. [24][25][26][27] In phage PVP-SE1, only 11 of the codons associated with its 24 tRNA genes were present at a frequency higher than in its Salmonella hosts.…”
Section: Codon Versus Amino Acid Usagementioning
confidence: 99%
“…DNA was precipitated with ethanol by adding 300 l of 3 M sodium acetate (Roth). SMRTbell template libraries were prepared according to instructions from Pacific Biosciences, Menlo Park, CA, USA, following the procedure and checklist for low-input 10-kb template preparation and sequencing by using C2-C2 chemistry as described previously (14).…”
mentioning
confidence: 99%
“…Subsequent studies have described the isolation and characterization of additional N4-like phages that infect a variety of bacterial species, including Vibrio, Pseudomonas, Salmonella, and Achromobacter spp. (17)(18)(19)(20)(21)(22)(23). With the exception of Enterobacter phage EcP1 (NC_019485), which has a relatively small capsid and genome, all N4-like phages characterized to date share morphologies, genome sizes, and genomic architectures similar to those of coliphage N4 (24).…”
mentioning
confidence: 99%